First photo evidence of stone marten Martes foina (Erxleben, 1777) in Rolwaling and Lapchi valleys of Gaurishankar Conservation Area, Nepal - Chetri, Madhu; Chaudhary, Bibash; Thami, Shankar Man (Nepalese Journal of Zoology, 2024)
Stone marten (Martes foina) is a fascinating, elusive and crepuscular small carnivore mammal belonging to the family Mustelidae. They are widely distributed throughout Europe and in western and central Asia. Little information is available on the distribution pattern and habitat requirement of the species in the Nepal Himalaya. Based on the camera trap study, we reported the first photo evidence of the presence of stone marten in the Lapchi and Rolwaling valleys of the Gaurishankar Conservation Area. This finding has opened new avenues for further ecological research and to investigate human-induced threats to the species in the region.